Reconsidering Our Dependent Variables: A Critique and Empirical Study - Staw, Barry M.; Oldham, Greg R. (Academy of Management Journal, 1978)
This paper builds a case for the refocusing of research away from the search for additional determinants of individual performance, turnover, and absenteeism, as now practiced in organizational research. Several new research directions are specified and, for one of these paths, a sample study is presented.